Analysis and Optimization of Saline-alkaline Water Comprehensive Utilization System. Issue 3 (May 2021) - Sun, Zhilin; Zhai, Chaoqun; Shu, Junwei
Abstract: On the basis of the previous field experiment and the actual situation in Xinjiang, four saline-alkaline water comprehensive utilization systems are proposed to optimize concentration and desalination process. Based on chemistry, thermodynamics and heat transfer, combined with economic costs and benefits, steam production and entransy are analyzed in this paper, the results show that the comprehensive efficiency of the dual heat source system is better than that of the single heat source system. Two-stage dual heat source system with series and parallel multi pass heat collecting has the best efficiency, but the comprehensive efficiency is similar to that of single-stage dual heat source system. These systems have their own strengths, which provide reference for brine treatment in salinization areas.